Tradisi Kafosulino Katulu Setelah Pelaksanaan Adat Pernikahan Etnik Muna Desa Parigi Kecamatan Parigi Kabupaten Muna - Wa Ode Sitti Maulana; Syahrun Syahrun; Komang Wahyu Rustiani (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2022)
Kafosulino katulu in the traditional wedding procession in the Muna community is a series of activities where the newlyweds return to the woman's parents' house. The objectives of this study were (1) to determine the process of implementing Kafosulino katulu in Parigi Village (2) to find out the functions contained in Kafosulino katulu in Parigi Village. (3) To find out the inheritance pattern of Kafosulino katulu in the Parigi Village community. Research Benefits. The results showed that in the process of implementing the Kafosulino Katulu tradition there were forms of presentation, namely 1) the process of washing feet 2) The process of wearing gloves 3) Kasambu. The process of implementing Kafosulino Katulu is carried out at the final stage of the wedding ceremony. In the pattern of inheritance of the Kafosulino Katulu tradition, namely through family inheritance, direct inheritance and inheritance in performances.